2005
DOI: 10.3182/20050703-6-cz-1902.00291
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Observability for Continuous Petri Nets

Abstract: Optimal observability of continuous Petri Nets consists in deciding the places to be measured (considering that all are measurable) such that the net system is observable and a cost function is minimal. Unfortunately this is not a simple covering problem. The results obtained in the paper are used in the implementation of an algorithm to improve the pure combinatorial search.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…As a direct consequence, it can be stated that a weighted T-system is observable for any initial marking iff all synchronization places are measured, or, in the case of a cycle, one arbitrary place is measured [48]. For this kind of nets, the rates of the transitions do not have any influence on the observability of the system.…”
Section: Observationmentioning
confidence: 97%
See 2 more Smart Citations
“…As a direct consequence, it can be stated that a weighted T-system is observable for any initial marking iff all synchronization places are measured, or, in the case of a cycle, one arbitrary place is measured [48]. For this kind of nets, the rates of the transitions do not have any influence on the observability of the system.…”
Section: Observationmentioning
confidence: 97%
“…To apply the previous result would mean to solve a combinatorial set of observability problems. Nevertheless this number can be greatly reduced in many cases applying the following property [48]: Let p and p be such that there is a path from p to p without synchronizations or attributions. Then -p can be deduced from the observation of p.…”
Section: Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…In Mahulea et al (2005) it is shown that if the net has attributions, i.e., p ∈ P with | • p| ≥ 2, observability can be lost. In this case, a pole-zero cancelation can appear, which happens for very specific values of λ, i.e., the denominator and the numerator of the transfer function vector between the input flow in places and the outputs:…”
Section: Generic Observabilitymentioning
confidence: 99%
“…In Mahulea et al (2005) an interpretation of the loss of observability in the case of join free (JF) contPN systems is given, when the system contains attributions. It is pointed out that observability cannot be checked locally and can be lost for some specific values of the firing rates of the transitions.…”
Section: Introductionmentioning
confidence: 99%